Newsreels - Kučera, Jan (Iluminace, 1990)
Radio lecture by film critic, theoretician and filmmaker Jan Kučera, broadcast under the title "How to make film journals" on the Prague station on 11 September 1935.
Keywords: newsreels; film weekly of the 1930s; radio and film